"Immunodiagnosis of Visceral Larval Migrans in Humans: Evaluation of an Enzyme-Linked Immunosorbent Assay" - Z Momeni; J Massoud; MB Rokni (Tehran University of Medical Sciences, 2003)
Human visceral and ocular toxocariasis can occasionally be a serious or life-threatening condition, especially for children. The diagnosis and confirmation of the disease mostly based upon serological tests. The purpose of the present study was to evaluate somatic antigen with regard to its application in a routine diagnostic laboratory test. Using gel-filtration chromatography, fraction No.1 of Toxocara canis antigen (F1To) was obtained from somatic antigen of parasite, and was evaluated for the immunodiagnosis of human toxocariasis by enzyme-linked immunosorbent assay (ELISA) test. Of 30 patients with suspected clinical toxocariasis, all had anti-T. Canis antibodies (positive serological result) corresponding to a diagnostic sensitivity of 100%. The specificity of the test was calculated as 77%. In this regard the positive and negative predictive values were demonstrated as 65.2% and 100% respectively. In conclusion, the application of the test using somatic antigen, because of the low specificity is not recommended.